2023
DOI: 10.1002/ptr.7763
|View full text |Cite
|
Sign up to set email alerts
|

The effects of phytochemicals on serum triglycerides in subjects with hypertriglyceridemia: A systematic review of randomized controlled trials

Abstract: This systematic review aimed to evaluate the efficacy of phytochemicals on lipid parameters in patients with hypertriglyceridemia (HTG). A comprehensive search was performed in PubMed/Medline, Scopus, ISI Web of Science, and Google Scholar from inception up to October 2021 to recognize randomized controlled trials (RCTs) assessing the effects of phytochemicals on lipid profiles in patients with HTG. Forty-eight RCTs including 53 arms and comprising 3,478 HTG patients met the eligibility criteria. Phytochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 146 publications
(309 reference statements)
0
4
0
Order By: Relevance
“…Many other systematic reviews of the use of curcumin to manage cholesterol and treat metabolic disorders can be found in refs . Results are overall positive.…”
Section: Curcumin As a Cholesterol Management Agentmentioning
confidence: 97%
See 1 more Smart Citation
“…Many other systematic reviews of the use of curcumin to manage cholesterol and treat metabolic disorders can be found in refs . Results are overall positive.…”
Section: Curcumin As a Cholesterol Management Agentmentioning
confidence: 97%
“…From the previous section, there are many reasons why curcumin-based FDC products are attractive for cholesterol management. Curcumin has been shown to inhibit key enzymes involved in the synthesis of cholesterol, such as HMG-CoA reductase. By reducing the activity of this enzyme, the production of cholesterol in the liver can be diminished.…”
Section: Challenges Of Using Curcumin-based Fdc Productsmentioning
confidence: 99%
“…Nevertheless, statin drugs may lead to adverse effects in patients using multiple medications, including muscle damage, renal failure, and myopathy; in addition, scholars have suggested some risk factors associated with statin toxicity, such as alcohol abuse, frailty, multisystem diseases, gender, and age . Many preclinical and clinical studies have reported that nutraceuticals and phytochemicals from plant-based products exhibit cholesterol-lowering properties and can be potentially used as alternative medication for lowering the risks of atherosclerosis-related diseases. , Therefore, researchers have encouraged the development of plant-based health products, including health food, functional food, and dietary supplements, containing nutraceuticals with hypocholesterolemic activity (as proven by their pharmacological effects) as a sustainable intervention to retard cholesterol increase . This review focuses on recent strategies and approaches to manage hypercholesterolemia using phytochemicals within 2019–2023.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the anti‐diabetic and anti‐lipidemic effects of this polyphenol have previously been confirmed (Ganji et al, 2021; Mahdavi et al, 2020; Mahdavi, Bagherniya, et al, 2021; Mahdavi, Moradi, et al, 2021; Parsamanesh et al, 2018; Rafiee et al, 2021; Talebi et al, 2020). This phytochemical also has healing effects in many liver‐related diseases, including non‐alcoholic fatty liver disease (NAFLD), hepatic steatosis, and liver fibrosis (Bagherniya et al, 2018; Dadkhah Tehrani et al, 2023; Farzaei et al, 2018; Feng et al, 2019; Hassanizadeh et al, 2023; Heidari et al, 2023; Jalali et al, 2020; Lee et al, 2019; Sharifi et al, 2023; Wu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%